Misogyny Traces Behind Powerful Female Representation In George R.R. Martin’s A Dance With Dragons (2011) - Maylda Auliffia Aztari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
In spite of the progress made toward gender equality, women are still subject to harassment on the basis of the traditional gender roles in today's society. This research is intended to analyze the depiction or representation of women in literary work in order to reveal misogyny lurking in the text. The novel used in this research is A Dance with Dragons novel (2011) by George R.R Martin. The issue of representation and misogyny tendencies are found in the novel. Qualitative research with a feminist approach was applied for the purpose to find the research objective which is to know the way Daenerys, Arya, and Melisandre are presented in the novel and to identify the misogyny lurking behind Daenerys, Arya, and Melisandre’s efforts to maintain their position. This analysis employs de Beauvoir’s Second Sex theory of women as “The Other”. The research reveals that behind the three powerful female characters, there is misogyny lurking behind Daenerys, Arya, and Melisandre's efforts in maintaining their powerful representation in George R.R. Martin’s A Dance with Dragons novel. The novel contains several examples of misogynist depictions, some of which include the objectification of women and an underestimation or undervaluation of female characters.